(untitled) (Ozone Therapy Global Journal, 2021)
Eosinophilic colitis is a variety of eosinophilic gastroenteritis. It is a rare disease of unknown etiopathogenesis that presents with eosinophilic infiltrates in the wall of the gastrointestinal tract. Its clinical manifestations are non-specific and diagnosis is based on the anatomopathological result of biopsy samples. Treatment has little evidence and is mainly based on dietary measures and the use of corticosteroids. Other drugs such as mast cell stabilizers, antihistamines, human antibodies, leukotriene antagonists and anti-IgE are also being tested but with limited data and efficacy. We present a clinical case of eosinophilic colitis treated effectively by rectal ozone insufflation, due to its local anti-inflammatory and immunomodulatory effect.